2015
DOI: 10.1016/j.jbvi.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Biology (prenatal testosterone), psychology (achievement need) and entrepreneurial impact

Abstract: a b s t r a c tEntrepreneurship holds the key to poverty alleviation and economic development. We find entrepreneurial impact as indicated by the number of jobs created by an entrepreneur is predicted by a biological factor -prenatal exposure to testosterone and a psychological factor -need for achievement. In a sample of 64 male German entrepreneurs we find that the interaction between prenatal exposure to testosterone and need for achievement predicted entrepreneurial impact. This study supports the idea tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…However, within the field of management, empirical studies have looked at only two of these five hormones: 25 studies examined testosterone, while 12 studies looked at cortisol. 3 This research has found significant associations between testosterone and numerous organizational phenotypes, such as entrepreneurial intention (Bönte, Procher, & Urbig, 2015), self-employment (Greene, Han, Martin, Zhang, & Wittert, 2014; Nicolaou, Patel, & Wolfe, in press; White et al, 2006), earnings (Gielen, Holmes, & Myers, 2016), leaders’ corruption (Bendahan, Zehnder, Pralong, & Antonakis, 2015), entrepreneurial performance (Unger, Rauch, Narayanan, Weis, & Frese, 2009; Unger, Rauch, Weis, & Frese, 2015), perceived empathic accuracy (Ronay & Carney, 2013), and firm performance (Trahms, Coombs, & Barrick, 2010) (see Figure S-3 in the online appendix). These findings reveal that testosterone is an important, but often overlooked, factor in explaining power and status in organizations, by driving people’s need to acquire additional resources and by stimulating competitive and retaliatory behaviors (Narayanan & Prasad, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, within the field of management, empirical studies have looked at only two of these five hormones: 25 studies examined testosterone, while 12 studies looked at cortisol. 3 This research has found significant associations between testosterone and numerous organizational phenotypes, such as entrepreneurial intention (Bönte, Procher, & Urbig, 2015), self-employment (Greene, Han, Martin, Zhang, & Wittert, 2014; Nicolaou, Patel, & Wolfe, in press; White et al, 2006), earnings (Gielen, Holmes, & Myers, 2016), leaders’ corruption (Bendahan, Zehnder, Pralong, & Antonakis, 2015), entrepreneurial performance (Unger, Rauch, Narayanan, Weis, & Frese, 2009; Unger, Rauch, Weis, & Frese, 2015), perceived empathic accuracy (Ronay & Carney, 2013), and firm performance (Trahms, Coombs, & Barrick, 2010) (see Figure S-3 in the online appendix). These findings reveal that testosterone is an important, but often overlooked, factor in explaining power and status in organizations, by driving people’s need to acquire additional resources and by stimulating competitive and retaliatory behaviors (Narayanan & Prasad, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they continuously learn and gain knowledge about the ways to improve their business network with key political and institutional actors. The autonomous decision-making power enables them to realize their social networking strategy and their drive to achieve makes them put extra efforts than their competitors in this regard (Frese and Gielnik, 2014; Lumpkin et al , 2009; Staniewski and Awruk, 2019; Unger et al , 2015). This kind of effective social networking plays a significant part in determining successful SME performance in emerging markets where the institutional framework is less developed and businesses are of considerably smaller size (Shafi et al , 2019; Stam et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, n Achievement is of particular interest in the context of SMEs because successful founder-managers in SMEs have distinctly different personality profiles than the successful managers of established, larger organizations (Ling et al , 2007). Indeed, successful SME owners are characterized by a relatively high level of n Achievement (Johnson, 1990; Unger et al , 2015). In a similar vein, McClelland (1965a) shows that n Achievement predicts both individual entrepreneurial activity and success, while n Achievement does not predict success in other career domains.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%